Agr polymorphisms and exotoxin production in Staphylococcus aureus - Sloan, Tim J. (2014)
Staphylococcus aureus is a highly successful human pathogen capable of colonising and spreading easily between humans while causing a wide range of infections, including life threatening bacteraemias, endocarditis and pneumonia. Virulence gene expression is regulated primarily by the staphylococcal accessory gene regulator (agr) in a cell density-dependent manner termed quorum sensing. Strains of S. aureus, particularly community-associated methicillin resistant S. aureus (CA-MRSA), carrying the genes for a pore forming exotoxin, the Panton Valentine Leukocidin (PVL), have been spreading worldwide over the last 10 to 15 years. As high level production of exotoxins has been implicated in the success of the CA-MRSA clone USA300, a collection of PVL producing clinical isolates from Nottingham were studied with the aim of understanding why PVL production might vary between strains.